Association between the Duration of Steroid Therapy with Hyperglycemia in Patients with Systemic Lupus Erythematosus (SLE) - Widyanrika, Farahdiva Audrey; Mudjanarko, Sony Wibisono; Rochmanti, Maftuchah; Ardiany, Deasy; Permana, Putu Bagus Dharma (Universitas Airlangga, 2024)
Introduction: Systemic Lupus Erythematosus (SLE) is a systemic autoimmune disease which primary treatment consists of steroid drugs administration. Prolonged steroid administration is often associated with an increase in blood glucose, a condition known as hyperglycemia. Hence, this study aimed to evaluate the association between the duration of steroid therapy with hyperglycemia in patients with SLE treated at a tertiary healthcare center in Surabaya, Indonesia.Methods: A cross-sectional study was conducted under a purposive sampling frame from January to December of 2022 by utilizing secondary data from electronic medical health records in Dr. Soetomo General Academic Hospital, a tertiary healthcare center in Surabaya, Indonesia. The association between variables were analyzed using Fisher's exact test, chi square test, independent T-test, one-way ANOVA, Mann-Whitney, and Spearman's rank correlation.Results: Out of 150 included patients, 2.67% experienced hyperglycemia following steroid therapy for SLE. There were no significant associations between clinical variables and hyperglycemia occurence in SLE patients (p>0.05). Patients that received higher doses of steroid did not experience any significant difference in hyperglycemia (p=0.727 for <6 months; p=0.865 for â‰¥6 months). Daily steroid dose was also not significantly associated with the severity of SLE manifestations based on the SLEDAI score (p=0.081). Overall, no significant association was identified between the duration of steroid therapy with hyperglycemia among SLE patients in the hospital (p=0.365). Conclusion: The study found no significant correlation between clinical variables, hyperglycemia incidence, daily steroids dosage, methylprednisolone dosage, SLE severity, or steroid use duration in patients with Systemic Lupus Erythematosus.